Photogrammetry for Implant Impressions: A Short Review - Alsmael, Mohammed A (Central Asian Journal of Medical and Natural Science, 2025)
Because of stitching mistakes and a lack of anatomical landmarks, intraoral scanners (IOS) frequently have trouble taking precise full-arch implant impressions, which results in less than ideal prosthetic fit. An alternative is provided by photogrammetry, which uses specialized cameras and coded scan bodies to directly record implant positions. Reviewing photogrammetry applications for full-arch, implant-supported prostheses with an emphasis on technical constraints, user experience, workflow efficiency, and accuracy is the goal. Using searches in PubMed, Google Scholar, and the Wiley Online Library, a narrative review of ten important studies was carried out. These studies included systematic reviews, in vitro comparisons, and proof-of-concept reports. Clinical trials and comparative studies comparing photogrammetry with IOS and traditional impression techniques were the focus of the inclusion criteria. Compared to IOS and traditional techniques, photogrammetry consistently showed sub-50 µm trueness in full-arch implant impressions. The "one-shot" capture method improved patient and clinician satisfaction by cutting down on scan time and retakes. The majority of systems, however, demand a different scan for soft-tissue registration, and there are still obstacles in the form of expensive upfront costs and a dearth of extensive clinical trials. The accuracy and effectiveness of full-arch implant workflows are greatly improved by photogrammetry. Despite its promise, its routine clinical adoption will require additional large-scale, standardized clinical studies and integrated soft-tissue capture solutions.